2010
DOI: 10.1097/hjh.0b013e32833310e0
|View full text |Cite
|
Sign up to set email alerts
|

The association between smoking and hypertension in a population-based sample of Vietnamese men

Abstract: In this population-based sample, hypertension was associated with smoking in a dose-response manner when characterized as number of years of smoking and lifetime cigarette consumption, but was not associated with current smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 36 publications
7
47
0
5
Order By: Relevance
“…Meanwhile, hypertension and smoking coexist more often than expected, which further amplifies risk of the CVD mortality [34,35]. Our previous study based on the same dataset revealed that there existed a synergistic interaction on an additive scale between current smoking and high SBP (140 mmHg) for the risk of coronary heart disease (CHD) in female adult population [36].…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, hypertension and smoking coexist more often than expected, which further amplifies risk of the CVD mortality [34,35]. Our previous study based on the same dataset revealed that there existed a synergistic interaction on an additive scale between current smoking and high SBP (140 mmHg) for the risk of coronary heart disease (CHD) in female adult population [36].…”
Section: Discussionmentioning
confidence: 95%
“…[15][16][17][18][19] There are few studies investigating the relationship between SHS exposure and BP among never smokers. A cross-sectional study involving clinically normotensive passive smokers found that selfreported passive smoking was associated with increased levels of BP in a dose-related manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although a clinically relevant effect of cigarette smoking on in-office blood pressure (BP) is controversial [1][2][3][4][5][6][7][8][9][10][11][12][13][14], as patients may refrain from smoking prior to office visits and cigarette smoking has relatively short-lived effects on BP [15][16][17][18][19], the major clinical impact of smoking on BP may not be accurately captured by in-office BP measurements. Indeed, despite a lack of relationship between smoking and in-office BP, a relationship between current smoking and out-of-office (24-h) BP has been reported on [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%